Challenges in classifying violent military offenses - Sobko, Ganna; Shchуrska, Victoria; Izotenko, Kateryna T.; Svintsytskyi, Andrii; Ponomarenko, Yuriy; Мулик, Катерина Тарасівна; Ізотенко, Катерина Тарасівна (Gruppo editoriale Tab S.r.l., 2025)
The article is devoted to the military doctrine of Ukraine, the main task of which is to ensure military security in the Armed Forces and other military organizations by performing special (security) services, namely: combat duty, combat service, border service, punitive service, watch service, public order and public security, internal service, and patrolling in the garrison. The article examines four corpus delicti of criminal offenses, which include: violation of the rules of combat duty (Article 420 of the Criminal Code of Ukraine); violation of the rules of border service (Article 419 of the Criminal Code of Ukraine); violation of the statutory rules of guard service or patrolling (Article 418 of the Criminal Code of Ukraine); violation of the statutory rules of internal service (Article 421 of the Criminal Code of Ukraine). This paper compares the military’s awareness of responsibility for violating an order with the expediency of taking into account the legal experience of international criminal tribunals. It also expresses the issue of dualistic legislative regulation of the duty of a serviceman to execute an order received in his address. Furthermore, it analyses the possibilities of resolving the conflict in terms of absolute necessity. Subsequent to this, the authors analyze in detail the corpus delicti of criminal offenses and their legislative constructions, as well as their important features in qualifying a criminal act. © 2025, Gruppo editoriale Tab S.r.l. All rights reserved.
Keywords: criminal offenses; military duty; military order; military statutory order of service